Barriers to research activities of faculty members in Islamic Azad University - Neshaneh Pakdaman; Mohammad Ali Ahmadi; Rakhshaneh Pakdaman; Narges Malih (Shahid Beheshti University of Medical Sciences, 2016)
Background: The present study was conducted to determine the inhibiting factors of research activities among the faculty members of Islamic Azad University.   Methods: In the present cross-sectional study, conducted between 2009-2013, 300 faculty members of Islamic Azad University, Science and Research Branch, Tehran, were selected following stratified random sampling method. Data collection instrument was a questionnaire comprising 20 questions about their research activities and 22 questions about their unwillingness to perform research activities.   Results: A total of 254 faculty members participated in the present study. About 15% of the participants were female. The findings of the current study showed that a) lack of physical space for work, study, and research, b) unfamiliarity with the searching methods on the Internet, and c) lack of sufficient familiarity with research methods and Statistics were the most important obstacles for the participant to carry out research projects.   Conclusion: Supporting the researcher financially and spiritually, considering the priorities and research needs, honoring the social status of faculty members, creating a calm and active environment for them, and removing encumbering administrative rules and regulations can help faculty members become eager to join in scientific research projects. Keywords: Faculty; Inhabiting Factors; Iran; Research; Universities